The impact of microinsurance on household welfare in South Africa - Magazi, Noluyolo (Graduate School of Business (GSB), 2020)
Despite recent economic growth over the last decade and high insurance penetration, the provision of insurance services to low-income households in South Africa is still neglected owing to pervasive information asymmetry. Even though households identify the importance of insurance, this has not translated into changed behaviour. According to KPMG, while 74% of households recognise their need for insurance, an overwhelming 34% lack any plans to address their perceived risk. Furthermore, there exists an incongruity between the perceived risks (such as job loss or loss of income) and the dominant insurance product in the market – which continues to be funeral cover. The study assessed the impact of microinsurance on the household welfare measured as household income per capita. The analysis draws on the nationally representative 2015 FINSCOPE survey, which contains in-depth data on the financial inclusion of 5000 households. Descriptive statistics were assessed to determine the nature of the identified variables and the relationship between them. The study performed multiple linear regression analysis using an Ordinary Least Squares (OLS) estimation. The empirical results provide evidence that microinsurance has a positive and significant effect on household welfare. Specifically, the results reveal that health and life insurance contribute favourably to household welfare, whilst credit life and funeral cover depict an inverse correlation. This suggests that health and life insurance better enable households to effectively manage risk and cope with adverse shocks. Furthermore, using household income per capita as a proxy for welfare, we observe that household size, dependency ratio, geographical location, gender of the household head, and marital status are statistically significant determinants of household welfare. Consistent with previous studies, where the educational attainment of the household head is at secondary and post-secondary level, households are empowered to utilise financial services to improve welfare and reduce incidence of poverty. Conventional insurance products do not appropriately serve the needs of lower income groups as often it is either too expensive or mismatched as coverage is possibly excessive, therefore we advocate for the creation of uniquely designed products and distribution systems that promote greater insurance inclusion for this segment of the market.